1989 Agricultural Research, Southeast Kansas Branch Station - L. W. Lomas; K. P. Coffey; J. L. Moyer; D. W. Sweeney; G. V. Granade; T. Walter; K. W. Kelley (Kansas Agricultural Experiment Station Research Reports, 1989)
Research on beef cattle and crops at Southeast Kansas Branch Station.
Keywords: beef cattle; forage; wheat; soybeans; alfalfa; sunflower; fescue; weeds; grain sorghum; soil; water management